Modified Boltzmann Factor on Rupture Probability - rizal kurniadi (Indonesian Journal of Physics, 2022)
Fission Products are data that is very much needed for developing nuclear technology. Considering that the experimental results of nuclear data are minimal, theoretical modeling and calculations are needed. One of the theoretical models is the "multimodal random neck-rupture model. (M-RNRM)" However, although it has completed the fission product data, it needs closer to the reference value. For this reason, the idea of modifying the Boltzmann factor on rupture probability was developed. This modification is in the form of adding a polynomial factor to the Boltzmann factor. This work has succeeded in showing better fission product calculation results closer to the reference value.